Manajemen Perpustakaan Masjid Al-Jihad dalam Meningkatkan Literasi Anak-Anak di Wilayah Rejang Lebong - Murniyanto Murniyanto (Tik Ilmeu: Jurnal Ilmu Perpustakaan dan Informasi)
The Al-Jihad Mosque library is the focus of this research. Management in this case places more emphasis on increasing children's literacy in the Rejang Lebong area, constraints and efforts to increase the effectiveness of handling literacy problems in children in the Rejang Lebong area. This research uses qualitative techniques, for data collection data, including observation, in-depth interviews, and documentation. The process of data analysis begins with data reduction, followed by polling, presentation, and drawing conclusions. By using technical triangulation and source triangulation, data validation was carried out. This study reveals that the Al-Jihad Mosque library is a source of information as well as a facilitator, mediator, and motivator as well as a non-formal educational institution. There are several limitations that become obstacles in efforts to increase literacy for children in Rejang Lebong district, including the lack of facilities, human resources, and the attention and interest of the local community. The solutions offered in reducing these obstacles include management improvements, then human resources, then infrastructure facilities, as well as the costs needed for the continuity of mosque library activities.